Estimation of latamoxef (moxalactam) dosage regimens against β-lactamase–producing Enterobacterales in dogs: a pharmacokinetic and pharmacodynamic analysis using Monte Carlo simulation - KUSUMOTO, Mizuki; NARITA, Haruka; MOTEGI, Tomoki; HARADA, Kazuki (Journal of Veterinary Medical Science, 2024)
One of the most significant research areas in veterinary medicine is the search for carbapenem substitutes for the treatment of extended-spectrum β-lactamase (ESBL)-producing Enterobacterales (ESBL-E). This study applied a pharmacokinetic/pharmacodynamic (PK/PD) strategy in validating optimal latamoxef (LMX) therapeutic regimens against canine ESBL-E infections. Five dogs were administered a bolus dose of 40 mg/kg LMX intravenously to measure serum drug concentrations and determine PK indices using the noncompartmental model. The highest minimum inhibitory concentration (MIC) with a probability of target attainment ≥90% was used to compute the PK/PD cutoff values for bacteriostatic (time for which the unbound drug concentration was above the MIC [fTAM] ≥ 40%) and bactericidal (fTAM ≥ 70%) effects when administered at 20, 30, 50, and 60 mg/kg, in addition to 40 mg/kg. The cumulative fraction of response (CFR) was determined using the MIC distribution of wild-type ESBL-E in companion animals. The PK/PD cutoff values can be increased by reducing the dosing interval rather than increasing the dose per time. Based on the calculated CFRs for ESBL-producing Escherichia coli and Klebsiella pneumoniae, all LMX regimens in this study and those administered at 30–60 mg/kg every 8 and 6 hr were found to be optimal (CFR ≥ 90%) for exerting bacteriostatic and bactericidal effects, respectively. However, the regimens of 50 and 60 mg/kg every 6 hr may merely exert bacteriostatic effects on ESBL-producing Enterobacter cloacae. Further clinical trials are required to confirm the clinical efficacy of LMX.